Genome‐wide identification of differential methylation between primary and recurrent hepatocellular carcinomas. Issue 7 (2nd July 2015) - Cui, Chenghua; Lu, Zheming; Yang, Liu; Gao, Yanhong; Liu, Wei; Gu, Liankun; Yang, Chen; Wilson, James; Zhang, Zhiqian; Xing, Baocai; Deng, Dajun; Sun, Zhong Sheng
Abstract : A biomarker capable of clinically predicting hepatocellular carcinoma (HCC) recurrence has not previously been established. Here genome‐wide differential methylation between primary and recurrent HCC cell lines (Hep‐11 and Hep‐12) from the same patient was characterized. The HCC samples from two independent cohorts, complete with follow‐up data, were used to validate the feasibility of the selected methylation biomarkers in predicting HCC prognosis. A methylation array assay identified 30 candidate genes or intergenic‐fragments with an absolute methylation fold‐change >2.0 between these cell lines; 22 candidates were hypomethylated in Hep‐12 cells relative to Hep‐11 cells. Bisulfite sequencing confirmed these results. Most importantly, classification of tumors by LINE‐2 methylation level was significantly associated with HCC recurrence in both cohorts ( P < 0.02). Similarly, MAD1L1 and LINC00682 methylation levels also correlated with HCC recurrence. Survival analysis showed that a combined baseline LINE‐2, MAD1L1, and LINC00682 methylation signature was significantly associated with short recurrence‐free survival in patients from both cohorts. A synergic effect was observed between these markers on both recurrence‐free survival ( P < 0.010) and overall survival ( P < 0.040). In conclusion, low levels of LINE‐2, MAD1L1, and LINC00682 methylation were associated with recurrence and decreased overall survival in HCC patients. © 2015 Wiley Periodicals, Inc.